2015
DOI: 10.1074/jbc.m115.677286
|View full text |Cite
|
Sign up to set email alerts
|

The Triggering Receptor Expressed on Myeloid Cells 2 Binds Apolipoprotein E

Abstract: Background: Mutations in the triggering receptor on myeloid cells 2 (TREM2) are associated with several neurodegenerative diseases, including Alzheimer disease, but the relevant TREM2 ligand is unknown. Results: TREM2 binds to apolipoprotein E (ApoE). Conclusion: TREM2 is a cellular receptor for ApoE. Significance: Identification of ApoE as a TREM2 ligand helps explain the role of TREM2 role in neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
249
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(278 citation statements)
references
References 37 publications
14
249
4
2
Order By: Relevance
“…More importantly, this process is dependent on the lipidation status of APOE, suggesting that apoE exerts its effects via manipulation of cellular cholesterol levels (87,140). More recently, the newly discovered AD risk gene that encodes the triggering receptor expressed on myeloid cells 2 (TREM2) (141,142) protein was found to have apoE as one of its ligands (143,144). Accordingly, TREM2-deficient microglia or microglia with an AD risk variant (R47H) lose the ability to effectively bind lipoproteins (including apoE), which decreases their phagocytic capabilities (145).…”
Section: Apoe and Cellular Metabolism Of Amentioning
confidence: 99%
“…More importantly, this process is dependent on the lipidation status of APOE, suggesting that apoE exerts its effects via manipulation of cellular cholesterol levels (87,140). More recently, the newly discovered AD risk gene that encodes the triggering receptor expressed on myeloid cells 2 (TREM2) (141,142) protein was found to have apoE as one of its ligands (143,144). Accordingly, TREM2-deficient microglia or microglia with an AD risk variant (R47H) lose the ability to effectively bind lipoproteins (including apoE), which decreases their phagocytic capabilities (145).…”
Section: Apoe and Cellular Metabolism Of Amentioning
confidence: 99%
“…TREM2 upregulation in such cells appears to accelerate their maturation and trafficking to lymph nodes and sites of infection, as well as stimulating the differentiation of Th2 or Th17 cells, dependent on the nature and concentration of the antigen presented [130,131]. The fact that TREM-2 acts as an ApoE receptor may also be of importance as this allows for an exaggerated effect of the ApoE4 protein in the context of dysfunctional TREM-2 receptors [132]. Moreover, a recent meta-analysis reported that increased methylation of the TREM2 promoter region appears to be an invariant feature in the brains of AD patients independently of age and sex [64].…”
Section: Influence Of Trem-2 Elevation In Pmbcsmentioning
confidence: 99%
“…There is also some evidence to suggest that increasing levels of neuroinflammation provoke further upregulation of the TREM-2 receptor on activated microglia allowing for an upwards spiral of inflammation via a positive feedback loop [153]. In addition, TREM-2 acts as an ApoE receptor [132], as discussed above, and in this context, it is noteworthy that recent studies have established a relationship between TREM-2 and ApoE in the regulation of the microglial phenotype and the level of inflammatory mediators excreted by these glial cells following activation [154,155]. In particular, evidence suggests that ApoE-mediated TREM-2 signalling provokes a change in microglial phenotype from tolerogenic to neurodegenerative following phagocytosis of apoptosed neurones in vivo [154] and the presence of the ApoE4 isoform is associated with higher levels of neuroinflammation in such circumstances by differentially increasing levels of TREM-2 [155].…”
Section: Abnormalities In Trem-2 Levels and Function As A Source Of Mmentioning
confidence: 99%
“…Recent accumulating evidence reveals an association between a diverse array of TREM2 variants and risk for AD and other neurodegenerative diseases [10][11][12]. These variants include mutations affecting TREM2 structure/function such as the generation of a truncated protein (W44X or W78X variants) [21], inability to associate with its intracellular adaptor, DAP12/TYROBP (K186N variant) [21], reduction in ligand binding ability (R47H variant) [22][23][24], alteration of subcellular localization (reduction on cell surface and increase in endoplasmic reticulum in T66M or Y38C variants) [18,25] and accelerated proteolytic loss from the cell surface (H157Y variant) [19,20]. Therefore, TREM2-related microglial dysfunction can potentially lead to the impairment of brain homeostasis including amyloid-β clearance, possibly leading to neuronal injury and cognitive dysfunction.…”
Section: Emerging Implications Of Trem2 and Strem2 In Neurodegeneratimentioning
confidence: 99%